Interrogative Clauses across CEFR Levels in Finnish and Swedish as an L2 - Toropainen Outi; Lahtinen Sinikka (Centre for Applied Language Studies, University of Jyväskylä, 2022)
The present study investigates the frequency of three types of interrogative clauses in 329 semi-formal email messages written by language learners of Finnish and of Swedish spoken in Finland. All the written messages were assessed according to the Common European Framework of Reference by trained language professionals. The study is part of a larger research project, Topling, conducted at the University of Jyväskylä. For the purpose of the study, the interrogative clauses were divided into three categories: yes/no questions, wh-questions and subordinate interrogative clauses. We examined the frequencies according to the levels of language proficiency. The findings show that, in both languages, the proportion of wh-questions decreased with increasing proficiency, while the proportion of subordinate clauses increased. This finding indicates that the interrogative clauses used at higher proficiency levels are more complex. Furthermore, the interrogative clauses were transformed into more polite requests concerning willingness and ability through the use of subordination as well as through the use of modal verbs (in Swedish) and the conditional mode (in Finnish).